Depolimerization of Sugarcane Bagasse by Microwave-assisted Pyrolysis - Joao C. S. Leite; Maria J. Suota; Luiz P. Ramos; Marcelo K. Lenzi; Luiz F. de Lima Luz Jr (Chemical Engineering Transactions, 2022)
Technologies and processes that minimize the dependence on petroleum products are among the most significant challenges of our time. Lignocellulosic biomass, such as sugarcane bagasse, is a promising alternative for obtaining a wide range of products, such as value-added chemicals and fuels. Pyrolysis is one of the most efficient ways to convert biomass into products with high calorific power, such as pyrolysis gas, bio-oil, and biochar. In this work, sugarcane bagasse with different moisture content (3.1 and 13.2%) was pyrolyzed using a microwave-assisted pyrolysis (MAP) system with silicon carbide (SiC) as a microwave absorber. The temperature profiles and fractions analysis helped to defining the best pyrolysis parameters: 23 min reaction time, 100% microwave power (644.70 Watts), 60 g of SiC, over setpoint temperature of 450 °C, and inert gas flow rate of 3 L/h. Analysis of the liquid fraction by GC-MS identified alcohols, aldehydes, carboxylic acids, and lignin derivatives in bio-oil composition. A slightly different bio-oil composition showed up for the sample with higher moisture content. Likewise, the solid fractions (biochar) were characterized by microscopy, showing a different surface morphology acording to the moisture content. In conclusion, MAP can be a promising alternative for achieving valuable magerials and small molecular mass compounds from sugarcane bagasse.